2018
DOI: 10.12659/msm.907441
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MiR-199b-5p Inducing Differentiation of Bone-Marrow Mesenchymal Stem Cells (BMSCs) Toward Cardiomyocyte-Like Cells via HSF1/HSP70 Pathway

Abstract: BackgroundBone-marrow mesenchymal stem cells (BMSCs) are pluripotent stem cells with potent self-renewal and differentiation ability that are widely used in transplantation of cell therapy. But the mechanism on microRNA (miRNA) regulating stem cell differentiation is complicated and unclear. The aim of this study was to investigate whether miR-199b-5p is involved in differentiation of cardiomyocyte-like cells and identify potential signal pathways in BMSCs.Material/MethodsMouse BMSCs were treated with 5-azacyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…In recent years, miRNAs have been shown to be involved in the occurrence, development and prognosis of various diseases, and have also been used to diagnose and treat diseases (17,18). miRNAs also regulate the differentiation of mesenchymal stem cells and osteoblasts (19,20). During the processes of bone differentiation and regeneration, abnormal miRNA expression is closely associated with OP (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, miRNAs have been shown to be involved in the occurrence, development and prognosis of various diseases, and have also been used to diagnose and treat diseases (17,18). miRNAs also regulate the differentiation of mesenchymal stem cells and osteoblasts (19,20). During the processes of bone differentiation and regeneration, abnormal miRNA expression is closely associated with OP (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…miR-146a-5p has been demonstrated to signi cantly induced VSMC proliferation [55], however, lack of miR-146a did not increase muscular dystrophy in mdx mice but was highly expressed in dystrophic muscle [79]. Decreased in the expression of miR-199b-5p induces differentiation of Bone-Marrow Mesenchymal Stem Cells (BMSCs) toward Cardiomyocyte-Like Cells [51]. The Knockdown of miR-199a-3p inhibits slow-to-fast muscle ber type change in mice and C2C12 Cells [80].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, notch signaling pathway has a known effect on cell differentiation via miRNAs. In previous studies, miR-199b-5p has been shown to be related with notch signaling pathway in various cell types including cancer (Chen et al, 2019;Dai et al, 2018;Won et al, 2013;Wu, Chen, Liu, Lai, & Liu, 2018;Zhao et al, 2016). Moreover, has also been involved in the certain pathologies process such as in ovarian cancer (Liu et al, 2014), medulloblastoma (Andolfo et al, 2012;Garzia et al, 2009), myocardial infarction (Duygu et al, 2017), and vascular pathologies (Briot et al, 2014).…”
Section: Jag1 Knockdown Promotes Differentiation and Could Block Thmentioning
confidence: 99%